Truth and Fake in the Post-Factual Digital Age: Distinctions in the Humanities and IT Sciences - Kar, Sanjoy (Journal of Data Science, Informetrics, and Citation Studies)
The book “Truth and Fake in the Post-Factual Digital Age: Distinctions in the Humanities and IT Sciences,” edited by Peter Klimczak and Thomas Zoglauer, presents a comprehensive exploration of the challenges posed by the surge in fake news and disinformation in the era of digitalization. Published by Springer in 2023, this work is a translation of the original German edition titled “Wahrheit und Fake im postfaktisch-digitalen Zeitalter,” published in 2021 by Springer Fachmedien Wiesbaden GmbH.